1962
DOI: 10.1063/1.1777170
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence of Landau Damping in Electron Beams

Abstract: Investigations have been made of plasma oscillations by studying space-charge waves in velocitymodulated electron beams. The convection current in a velocity-modulated slowly-drifting electron beam was measured as a function of distance from the modulating cavity. The experiments indicate that in the presence of an appreciable velocity spread, the fast space-charge wave is damped while the slow space-charge wave remains unattenuated. The measurements were made under conditions where the velocity spread is domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1964
1964
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…11 ' 12 A spatially periodic interference pattern results along the beam, with minima at every half-plasma wavelength, if both waves are excited with equal amplitude. 13 Such patterns are clearly indicated from the experimental results of Beam 14 , and Caulton et al 10 The fundamental plasma wavelength varies with both beam current and drift potential. Therefore, as the delay is varied by altering the drift space potential the amplitude of the output signal (gain) will vary.…”
Section: December 1964mentioning
confidence: 82%
See 2 more Smart Citations
“…11 ' 12 A spatially periodic interference pattern results along the beam, with minima at every half-plasma wavelength, if both waves are excited with equal amplitude. 13 Such patterns are clearly indicated from the experimental results of Beam 14 , and Caulton et al 10 The fundamental plasma wavelength varies with both beam current and drift potential. Therefore, as the delay is varied by altering the drift space potential the amplitude of the output signal (gain) will vary.…”
Section: December 1964mentioning
confidence: 82%
“…Such a phenomenon is referred to as Landau damping 15 and has been analysed by Dawson 16 and Berghammer 13 and experimentally verified by Caulton et al 10 Berghammer has shown that the decay of the velocity modulation is attributable to a spatial Landau damping of the 'fast' space-charge wave.…”
Section: December 1964mentioning
confidence: 93%
See 1 more Smart Citation
“…In some of the electron beam experimcntal work on this problem (Caulton et al 1962, Mihran 1962, it has been assumed, with good reason, that velocity spreads of the order of 10% of the beam velocity were present and the parameter (w,,/wO)2 was of the order of 10-3 . Accordingly, for numerical solution we have chosen these numbers and the velocity distribution:…”
Section: Problem Of the Experimental Confirmation Of Landau Damping 407mentioning
confidence: 99%